MORPHOLOGICAL CHARACTERS OF FRESHWATER STINGRAYS (CHONDRICHTHYES: DASYATIDAE) IN MUSI RIVER, PALEMBANG CITY, SOUTH SUMATERA PROVINCE - Amran Halim; Hilda Zulkifli; Yuanita Windusari (BIOVALENTIA: Biological Research Journal, 2022)
A study to determine morphological characets of freshwater stingray in Musi River of South Sumatra Province has been conducted from June to December 2020. The fishes were collected in Musi River where located at middle of Palembang city. Collected specimens were preserved to Animal Ecology Laboratory, Department of Biology, Faculty of Mathematic and Natural Science of Sriwijaya University. There are four species of freshwater stingrays collected, Fluvitrygon oxyrhyncha. Fluvitrygon kittipongi. Fluvitrygon signifer, and Fluvitrygon sp ‘musi’ 2. The results of the measurement of morphometric and morphological characteristics showed that there were differences in size and morphological characteristics of the types of fish found, indicating that stingray had different size ranges.